-12 + 9 - (-3) - 11
Remember PEMDAS: This is the order of operation.
P-Paragrahp
E-Exponent
M-Multiply
D-Divide
A-Add
S-Subtract
1st step: PEM
-(-3) is actually -1 * -3 = + 3
-12 + 9 + 3 - 11
2nd step: D is not possible, so we do A.
9 + 3 = 12
3rd Step: Subtract
12 - 12 - 11 = 0 - 11 = -11 CHOICE B.
He scored 24 points which means that after scoring the 4 three pointers, he would have to score another 4 three pointers (12 points)
Answer:
1.) f(x) = x*x - 7x + 10
2.) f(x) = x*x - 5x
3.) f(x) = 4*x*x - 5x - 6
4.) f(x) = 6*x*x -5x + 1
Step-by-step explanation:
1.) 2 and 5 (x -2)(x - 5) = f(x) = x*x - 7x + 10
2.) 0 and 5 f(x) = x*(x -5) = x*x - 5x
3.) -3/4 and 2 (x + 3/4)(x -2) = x*x - (5/4) x - 3/2,
need integers f(x) = 4xx - 5x - 6
4.) 1/2 and 1/3 (x - 1/2)(x - 1/3) = f(x)
x*x - 1/3 x - 1/2 x + 1/6
xx - 5/6 x + 1/6
6 xx - 5x + 1
Answer:
the answer is D. 613.44
Step-by-step explanation:
<u><em>D..............</em></u>
Answer is SSA (first choice)
cause LE perpendicular to BU so LEB = LEU = 90
hope it helps